Control de Inventarios de activos corrientes en la bodega de la empresa municipal de agua potable y alcantarillado San Miguel (EMAPA-SM) en el año 2017 - Zurita Romero, Joseline Anntonelly (2018)
The purpose of this project is to analyze the Control of Inventories in the Cellar of the Municipal Company of Drinking water and Sewer system of the Canton San Miguel. From the beginnings in the Creation of the Company a good control of the inventories has not been taken in alone cellar he/she usually registers with kardex a registration that is not very appropriate for a good administrative administration. At the moment he/she has not been carried out a diagnosis of this inventories the registrations they are presented annually to the pertinent authorities of the company this will be good me as an instrument for my investigation of Control of Inventories and this way to improve the quality of administrative administration. The methodology that was used in the present investigation, was by means of the Deductive and Inductive method, the investigation types were of: Field, Descriptive, Qualitative, Quantitative and documental, the universe to which was carried out the investigation corresponds 18 workers between Administrative and Operative that realized the situation in which is the cellar area and the administrative administration in the company through the same ones. To reach the results that they possess the investigation work statistically, for their formulation and interpretation, it was developed in the following way: Informative data, Fear, Records, General Objective and three Specific that help me to the execution of the general objective, Theoretical Marco that I help myself end up knowing the reasons for which the EMAPA-SM needs a Control of Inventories considerably in Cellar, Hypothesis or he/she Asks, Variables, Methodology, Types of Investigation, Technical and Instruments for the Obtaining of Data, Universe. With the application of this investigation the Company will be able to possess an excellent Administrative Administration because it will no longer exist surpluses of materials in Cellar. With the effective and efficient control it will be achieved that all the materials are used and reutilizados in due form